ANALISIS RANTAI PASOK CABAI BESAR DI KABUPATEN MERANGIN - Endi Harmoko; DMT. Napitupulu; Mirawati Yanita (Agripita: Jurnal Agribisnis dan Pembangunan Pertanian, 2020)
The purposes of this study are 1.) Describe the large chili supply chain. 2) Analyze the performance of large chili supply chains. This research was conducted in Jangkat and Jangkat Timur Districts of Merangin Regency from March to May 2019. Farmers 'samples were determined by simple random methods while traders' samples were determined by snowball sampling. The data analysis method includes a qualitative descriptive analysis with the Food Supply Chain Network (FSCN) framework to analyze the supply chain picture, while marketing analysis is to analyze supply chain performance by calculating marketing margins, farmer share, and marketing efficiency values. The results showed a large chili supply chain in Merangin District in the form of a network with the aim of the domestic market. The supply chain structure consists of five members, namely farmers, small traders, large traders, retailers and consumers. There are three supply chain channels, namely I (Farmer-retailer-consumer trader), II (farmer-small-trader-large-trader-retailer-consumer trader) III (farmer-large-trader-retailer-consumer trader). The implementation of supply chain management has not gone well and the available resources are still limited. Business processes in the large chili supply chain are not running because the information flow is not smooth. The cycle that is run in a business process is the procurement cycle. Supply chain performance results of the marketing aspect analysis show that the finalized marketing margin is on channel one of Rp. 6000. Farmer's highest share is in channel one of 85.25%. The lowest marketing efficiency value is in channel one of 4.14%, this shows that the performance of the large chili supply chain in Merangin Regency has run efficiently.